Faster Multistep Iterations for the Approximation of Fixed Points Applied to Zamfirescu Operators - Shin Min Kang; Ljubomir B. Ćirić; Arif Rafiq; Faisal Ali; Young Chel Kwun (Abstract and Applied Analysis)
By taking a counterexample, we prove that the multistep iteration process is faster than the Mann and Ishikawa iteration processes for Zamfirescu operators.